Comparative effects of liraglutide and dapagliflozin on lipid profile and cardiovascular risk in patients with metabolic dysfunction-associated steatotic liver disease and type 2 diabetes: a 6-month randomized study - Akimov, Artem; Cherniavskyi , Volodymyr (The Ukrainian Scientific Medical Youth Journal, 2025)
Metabolic dysfunction-associated steatotic liver disease frequently coexists with type 2 diabetes mellitus, resulting in increased cardiometabolic risk. Pharmacologic agents such as glucagon-like peptide-1 receptor agonists and sodium-glucose cotransporter-2 inhibitors may improve lipid metabolism and cardiovascular outcomes, but comparative data remain limited. Aim: To evaluate and compare the magnitude of change (delta values) in lipid profile parameters and cardiovascular risk scores, assessed using five validated stratification tools, in patients with ьetabolic dysfunction-associated steatotic liver disease and type 2 diabetes mellitus following 6-month treatment with liraglutide or dapagliflozin. Materials and Methods: This 6-month prospective, randomized study included 72 patients with metabolic dysfunction-associated steatotic liver disease and type 2 diabetes mellitus allocated to three groups: control (lifestyle intervention; n=23), dapagliflozin (10 mg daily; n=26), or liraglutide (up to 1.8 mg daily; n=23). Lipid profiles and cardiovascular risk were assessed at baseline and after treatment using five validated tools (Globorisk, Framingham Risk Score, ASCVD Risk Calculator, PROCAM, WHO CVD chart). Intergroup comparisons were based on changes from baseline. Results: All groups showed significant within-group improvements in lipid parameters, with reductions in total cholesterol, low-density lipoproteins, and triglycerides and increases in high-density lipoproteins (p<0.001). The liraglutide group demonstrated greater improvements in total cholesterol, low-density lipoproteins, and high-density lipoproteins compared to control and dapagliflozin (p<0.01). Cardiovascular risk scores declined significantly within each group. Between-group comparisons revealed significant differences for the Framingham score (favoring liraglutide over control) and the PROCAM score (favoring both pharmacologic treatments over control). No consistent differences were observed between liraglutide and dapagliflozin across other risk models. Conclusions: Both liraglutide and dapagliflozin improved lipid profiles and reduced cardiovascular risk in patients with metabolic dysfunction-associated steatotic liver disease and type 2 diabetes mellitus. Although no statistically significant superiority of liraglutide over dapagliflozin was confirmed for cardiovascular risk scores, a consistent trend toward greater lipid improvement was noted. Further studies with larger samples and longer follow-up are needed to clarify these findings.